PERLINDUNGAN KONSUMEN SEKTOR JASA KEUANGAN ATAS PENYALAHGUNAAN DATA PRIBADI PADA APLIKASI KREDIT ONLINE - Aldi Rinaldi; Ermanto Fahamsyah (Jurnal Hukum Adigama, 2020)
A Fintech product is a combination of finance and information technology. Fintech adapted the principles of computer networks that are expected to make financial transaction processes more efficient and easier. Through a simple submission process, Fintech is a matter of public interest as a consumer as well as a business opportunity. As a fintech organizer, it is obligatory to protect personal data based on the principle of good personal data protection. Based on the Financial Services Authority Regulation No. 77 / POJK.01 / 2016, it is not related to the procedure or procedure for collection (collection) of Debt Loan payments by Loan Recipients. However, every effort to collect Debt Loans from Loan Recipients must be approved and approved in other applicable conditions. The collection of Debt Loan collections from Loan Recipients does not run in accordance with the existing provisions. Many cases when carrying out the collection (collection) of loan payments, the lender performs obligations to existing provisions and collects personal data of consumers to carry out billing (collection) as there is where confidentiality of personal data of consumers is not necessary. In fact the Personal Data Protection Act must be immediately passed to provide a strong legal basis for the protection of the public (consumers) for actions that harm Business Actors who do not have good faith in the effort.